Production of tempe koro benguk using local starter and its implementation as a biotechnology module for high school students - Septiani, Aulia; Mamangkey, Jendri; Adinugraha, Fajar; Mendes, Lucas William (Universitas Islam Negeri Sumatera Utara, 2024)
The Kurikulum Merdeka emphasizes integrating local wisdom into education to develop students’ soft skills and character. Traditional foods like koro benguk tempe (TKB), a fermented product made from Mucuna pruriens (L.) DC. from Dimoro Village, Central Java, offer an excellent avenue for such integration in biotechnology education. A survey at Yadika 4 High School revealed a lack of local wisdom-based practical guides, demanding the need for resources that could enhance student engagement in biotechnology knowledge. This study developed practical guidelines for TKB production, focusing on its organoleptic properties, integration feasibility, and feedback from teachers and students. Laboratory experiments and module development were combined to collect data. Organoleptic tests identified 0.3% starter concentration as optimal, producing tempe with a white color, soft texture, and pleasant taste. The practical guidelines achieved a validation score of 89% from language, material, and media experts, while teachers rated them at 90%, and students responded positively with a 73% score. Further research is needed to refine the fermentation process of TKB beyond 36 hours and analyze its pH content. Expanding the study to include other fermented local products could further enhance biotechnology learning. Integrating local wisdom through practical guides not only promotes cultural preservation but also improves students' memory, manipulative skills, creativity, communication, and responsibility.